Tinjauan Yuridis terhadap Delik Aduan dalam Penegakan Hukum Hak Cipta berdasarkan Undang-Undang Nomor 28 Tahun 2014 - Lutfi Yusup Rahmathoni; Sri Herlina; Sudiyono Sudiyono; Ahmad Rizqi (Jurnal Hukum Lex Generalis, 2025)
This study examines the application of complaint offenses in copyright law enforcement under Law Number 28 of 2014 concerning Copyright. As part of intellectual property rights, copyright provides legal protection for creative works, enabling creators or rights holders to obtain both economic and moral benefits, and preventing violations such as piracy or unauthorized use. Based on Article 120 of the Copyright Law, most copyright violations are classified as complaint offenses, meaning that investigation and prosecution can only proceed if a complaint is filed by the creator, copyright holder, or an authorized party unless the violation harms the public interest, in which case it is treated as an ordinary crime. This study employs a descriptive-analytical approach to primary, secondary, and tertiary legal materials. The findings indicate that the regulation of complaint offenses offers flexibility for rights holders to choose between litigation and non-litigation resolution. However, implementation faces challenges such as proving ownership, lengthy legal processes, and the potential misuse of complaint withdrawals. In conclusion, applying the complaint offense mechanism to copyright law can balance the protection of individual rights with the public interest, but it requires stronger regulations and greater legal awareness to achieve more effective and equitable enforcement.